Comparative efficacy and safety of second-line antiretroviral therapy for treatment of HIV/AIDS: a systematic review and network meta-analysis. Issue 10 (October 2017) - Kanters, Steve; Socias, Maria Eugenia; Paton, Nicholas I; Vitoria, Marco; Doherty, Meg; Ayers, Dieter; Popoff, Evan; Chan, Keith; Cooper, David A; Wiens, Matthew O; Calmy, Alexandra; Ford, Nathan; et al.
Summary: Background: Selection of optimal second-line antiretroviral therapy (ART) has important clinical and programmatic implications. To inform the 2016 revision of the WHO ART guidelines, we assessed the comparative effectiveness and safety of available second-line ART regimens for adults and adolescents in whom first-line non-nucleoside reverse transcriptase inhibitor (NNRTI)-based regimens have failed. Methods: In this systematic review and network meta-analysis, we searched for randomised controlled trials and prospective and retrospective cohort studies that evaluated outcomes in treatment-experienced adults living with HIV who switched ART regimen after failure of a WHO-recommended first-line NNRTI-based regimen. We searched Embase, MEDLINE, and the Cochrane Central Register of Controlled Trials for reports published from Jan 1, 1996, to Aug 8, 2016, and searched conference abstracts published from Jan 1, 2014, to Aug 8, 2016. Outcomes of interest were viral suppression, mortality, AIDS-defining illnesses or WHO stage 3–4 disease, discontinuations, discontinuations due to adverse events, and serious adverse events. We assessed comparative efficacy and safety in a network meta-analysis, using Bayesian hierarchical models. Findings: We identified 12 papers pertaining to eight studies, including 4778 participants. The network was centred on ritonavir-boosted lopinavir plus two nucleoside or nucleotide reverse transcriptase inhibitors. Ritonavir-boosted lopinavir monotherapy was the only regimen inferior to others. With the lower estimate of the 95% credible interval (CrI) not exceeding the predefined threshold of 15%, evidence at 48 weeks supported the non-inferiority of ritonavir-boosted lopinavir plus raltegravir to regimens including ritonavir-boosted protease inhibitor plus two NRTIs with respect to viral suppression (odds ratio 1·09, 95% CrI 0·88–1·35). Estimated efficacy of ritonavir-boosted darunavir (800 mg once daily) was too imprecise to determine non-inferiority. Overall, regimens did not differ significantly with respect to continuations, AIDS-defining illnesses or WHO stage 3–4 disease, or mortality. Interpretation: With the exception of ritonavir-boosted lopinavir plus raltegravir, the evidence base is unable to provide strong support to alternative second-line options to ritonavir-boosted protease inhibitor plus two NRTIs, and thus more trials are warranted. Funding: WHO.